qualitative and quantitative HPTLC densitometry method for the analysis of cannabinoids in Cannabis sativa L - Fischedick, Justin T; Glas, Ronald; Hazekamp, Arno; Verpoorte, Rob (Phytochemical analysis, 2009)
Introduction - Cannabis and cannabinoid based medicines are currently under serious investigation for legitimate development as medicinal agents, necessitating new low-cost, high-throughput analytical methods for quality control.Objective - The goal of this study was to develop and validate, according to ICH guidelines, a simple rapid HPTLC method for the quantification of Δ⁹-tetrahydrocannabinol (Δ⁹-THC) and qualitative analysis of other main neutral cannabinoids found in cannabis.Methodology - The method was developed and validated with the use of pure cannabinoid reference standards and two medicinal cannabis cultivars. Accuracy was determined by comparing results obtained from the HTPLC method with those obtained from a validated HPLC method. Results - Δ⁹-THC gives linear calibration curves in the range of 50-500 ng at 206 nm with a linear regression of y = 11.858x + 125.99 and r² = 0.9968.Conclusion - Results have shown that the HPTLC method is reproducible and accurate for the quantification of Δ⁹-THC in cannabis. The method is also useful for the qualitative screening of the main neutral cannabinoids found in cannabis cultivars. Copyright © 2009 John Wiley '' Sons, Ltd.